Epiregulin promotes osteogenic differentiation and inhibits neurogenic trans‐differentiation of adipose‐derived mesenchymal stem cells via MAPKs pathway. (26th January 2020) - Cao, Yangyang; Shi, Ruitang; Yang, Haoqing; Zhang, Jianpeng; Ge, Lihua; Gao, Runtao; Fan, Zhipeng
Abstract: Mesenchymal stem cells (MSCs) exists low efficiency to trans‐differentiate into other germinal layer cell types. One key issue is to discover the effect of important factor on MSCs differentiation abiltiy. In this study, we investigated the role and mechanism of epiregulin (EREG) on the osteogenic differentiation and neurogenic trans‐differentiation in adipose‐derived stem cells (ADSCs). We discovered that the depletion of EREG inhibited the osteogenic differentiation in vitro. And 25 ng/mL recombinant human epiregulin protein (rhEREG) effectively improved the osteogenic differentiation of EREG‐depleted‐ADSCs. Depletion of EREG promoted the formation of neural spheres, and increased the expressions of nestin, βIII‐tubulin, NeuroD, NCAM, TH, and NEF in ADSCs. Then, 25 ng/mL rhEREG significantly inhibited these neurogenic differentiation indicators. Inhibition of p38 MAPK, JNK, or Erk1/2 signaling pathway separately, blocked the rhEREG‐enhanced osteogenic differentiation ability and the rhEREG‐inhibited neurogenic trans‐differentiation ability of ADSCs. In conclusions, EREG promoted the osteogenic differentiation and inhibited the neurogenic trans‐differentiation potentials of ADSCs via MAPK signaling pathways.